2018
DOI: 10.1029/2018gb005887
|View full text |Cite
|
Sign up to set email alerts
|

Global Nitrous Oxide Production Determined by Oxygen Sensitivity of Nitrification and Denitrification

Abstract: The ocean is estimated to contribute up to ~20% of global fluxes of atmospheric nitrous oxide (N2O), an important greenhouse gas and ozone depletion agent. Marine oxygen minimum zones contribute disproportionately to this flux. To further understand the partition of nitrification and denitrification and their environmental controls on marine N2O fluxes, we report new relationships between oxygen concentration and rates of N2O production from nitrification and denitrification directly measured with 15N tracers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
127
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(174 citation statements)
references
References 58 publications
25
127
4
Order By: Relevance
“…Furthermore, N 2 O was undersaturated at anoxic depths, indicating net N 2 O consumption as a result of complete denitrification. Both NO 3 − and NO 2 − reduction to N 2 O can be regarded as partial denitrification; however, it has been shown that the two pathways were performed independently by denitrifying cells, and intracellular exchange of NO 2 − was not detected (Ji et al, 2018). Thus, rates of NO 3 − and NO 2 − reduction to N 2 O were measured separately, and it is unnecessary for the two sets of rates to match.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, N 2 O was undersaturated at anoxic depths, indicating net N 2 O consumption as a result of complete denitrification. Both NO 3 − and NO 2 − reduction to N 2 O can be regarded as partial denitrification; however, it has been shown that the two pathways were performed independently by denitrifying cells, and intracellular exchange of NO 2 − was not detected (Ji et al, 2018). Thus, rates of NO 3 − and NO 2 − reduction to N 2 O were measured separately, and it is unnecessary for the two sets of rates to match.…”
Section: Discussionmentioning
confidence: 99%
“…The analyses of natural abundance bulk N 2 O isotopes ( 15 N versus 14 N and 18 O versus 16 O) and isotopomers (the intramolecular configuration of nitrogen isotopes within the linear N 2 O molecule) provide a further indication of how the different metabolic pathways have contributed to total N 2 O production in Saanich Inlet. For example, 15 N tracer experiments determine potential and instantaneous N 2 O production rates and pathways (Ji et al, 2018), whereas N 2 O isotopomeric measurements reveal the dominant N 2 O production pathway integrated over the history of a water mass (Fujii et al, 2013). The isotope measurements reported here were conducted on a recently developed laser‐based analytical system that is able to deliver accuracy and precision comparable to traditional isotope ratio mass spectrometer techniques (Ji & Grundle, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In response to this global deoxygenation, subsurface oxygen minimum zones (OMZs) are expected to expand, bringing very low oxygen waters closer to the ocean surface (Oschlies et al, ). These changes in the depth of the OMZ upper boundary could have severe impacts on marine life and biogeochemical cycling (Gruber, ; Levin, ), such as the compression of the habitat of commercially fished species and related ecosystems (Chu & Tunnicliffe, ; Sperling et al, ; Stramma et al, ), the reduction of carbon export by migrating zooplankton (Bianchi et al, ), and the release of nitrous oxide to the atmosphere (Arévalo‐Martínez et al, ; Babbin et al, ; Ji et al, ; Yang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This process is also promoted under micro-oxic and anoxic conditions (Yu et al, 2010). Denitrification by heterotrophic denitrifiers is another major pathway of N 2 O production in marine environments, occurring under anoxic conditions or at the suboxic-anoxic interface (Naqvi et al, 2010;Yamagishi et al, 2007;Ji et al, 2018). NO − 2 is reduced by a coppercontaining (NirK) or cytochrome-cd1-containing (NirS) nitrite reductase to nitric oxide (NO) and then by a hemecopper NO reductase (NOR) to N 2 O (Coyne et al, 1989;Treusch et a1., 2005;Abell et al, 2010;Bartossek et a1., 2010;Lund et a1., 2012;Graf et al, 2014).…”
Section: Introductionmentioning
confidence: 99%